Pengaruh Belajar Kelompok Dan Bimbingan Belajar SekolahTerhadap Prestasi Belajar Siswa pada Mata Pelajaran Ipa Kelas atas SD Muhammadiyah 22 Sruni Surakarta Tahun 2015/2016 - Oktaviana, Ika Indriani; , Minsih, S. Ag. M. Pd (2016)
The purpose of this study was to determine include: 1) Effect of group learning on student achievement in science subjects upscale 22 Sruni SD Muhammadiyah Surakarta year 2015/2016, 2) Effect of tutoring schools on student achievement in science subjects classroom over 22 Sruni in SD Muhammadiyah Surakarta year 2015/2016, 3) How much influence the group learning and tutoring schools on student achievement in science subjects upscale SD Muhammadiyah Surakarta 22 Sruni year 2015/2016. Effect of group learning and tutoring schools on student achievement upscale 22 Sruni SD Muhammadiyah Surakarta year 2015/2016. This type of research is based on a quantitative approach to the type of research Ex-Post Facto. The analysis technique used is multiple linear regression, t test. Based on the analysis of data: 1) the equation obtained regression coefficient is Y = 50,481+ 0.235 X1 + 0.326 X2. 2) Test Results T Study Group thitung (3.832)> t table (2.024), study group positive effect on student achievement. 3) The school tutoring positive effect on student achievement, it is based on t test results tcount (4.495)> t table (2.024).